An Effective Christian Presence. (2nd July 2016) - Clark, Elizabeth
Abstract : The Methodist Conference used the term 'Effective Christian Presence' in a report of 2004 with specific reference to rural communities. In the light of the known challenges facing rural areas and rural churches, this article explores ways to give substance to the concept of effectiveness in community. Ecumenical working is understood to be key, as is the necessity of moving beyond an exclusive focus on buildings. Equipping Christians to integrate their faith into the practices of daily life is central to effectiveness and this can be understood as simultaneously priestly, prophetic and evangelistic. All three are explored in greater depth, and the article concludes that by holding them together the rural church becomes well-equipped to offer the kind of supportive relationships that are increasingly sought after as a reaction to the individualism of contemporary culture.